Proceedings of the 2017 SIAM International Conference on Data Mining 2017
DOI: 10.1137/1.9781611974973.21
|View full text |Cite
|
Sign up to set email alerts
|

Unified and Contrasting Graphical Lasso for Brain Network Discovery

Abstract: The analysis of brain imaging data has attracted much attention recently. A popular analysis is to discover a network representation of brain from the neuroimaging data, where each node denotes a brain region and each edge represents a functional association or structural connection between two brain regions. Motivated by the multi-subject and multi-collection settings in neuroimaging studies, in this paper, we consider brain network discovery under two novel settings: 1) unified setting: Given a collection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Brain extraction (a.k.a. skull stripping), registration and segmentation serve as preliminary yet indispensable steps in many neuroimaging studies, such as anatomical and functional analysis [4,33,50,52], brain networks discovering [11,24,27,28,53,54], multi-modality fusion [6,26], diagnostic assistance [18,46], and brain region studies [8,25]. The brain extraction targets the removal of non-cerebral tissues (e.g., skull, dura, and scalp) from a patient's head scan; the registration step aims to align the extracted brain with a standard brain template; the segmentation step intends to label the anatomical brain regions in the raw imaging scan.…”
Section: Introductionmentioning
confidence: 99%
“…Brain extraction (a.k.a. skull stripping), registration and segmentation serve as preliminary yet indispensable steps in many neuroimaging studies, such as anatomical and functional analysis [4,33,50,52], brain networks discovering [11,24,27,28,53,54], multi-modality fusion [6,26], diagnostic assistance [18,46], and brain region studies [8,25]. The brain extraction targets the removal of non-cerebral tissues (e.g., skull, dura, and scalp) from a patient's head scan; the registration step aims to align the extracted brain with a standard brain template; the segmentation step intends to label the anatomical brain regions in the raw imaging scan.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in network analysis have allowed new insights for our understanding of complex networks and interactions (i.e., connectivity patterns) within each network. A human brain can be modeled as a complex network, containing a number of structurally/functionally interconnected brain regions (Power et al 2010;Liu, Kong, and Ragin 2017). Generally, a brain network (a.k.a., connectome) can be characterized by a set of nodes and edges, where nodes represent regions-of-interest (ROIs) in the brain and edges denote the connectivity strength or correlation between brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…Electroencephalographic (EEG) recording of neural activity has been used widely for sleep monitoring and diagnosis of sleep disorders [1] [2] [3] [4]. EEG activity in the α band (8)(9)(10)(11)(12) Hz) has long been associated with wakefulness with power attenuating and becoming sporadic during the Sleep Onset Process (SOP) [2] [5], then disappearing at the onset of sleep. Bursts of α activity have also been observed during and around [1] Rapid Eye Movement (REM) sleep.…”
Section: Introductionmentioning
confidence: 99%
“…Varoquaux et al proposed a population prior to address the variability among subjects when estimating the brain covariance matrix during spontaneous brain activity [9]. To identify the brain network alterations among HIV patients and healthy controls, Liu et al constructed a contrasting framework and observed major differences in the occipital lobe and parietal lobe [10]. To discover the default mode alterations in schizophrenia, Lefort-Besnard et al employed sparse inverse covariance estimation method and identified a statistically significant difference between healthy controls and patients in the default mode network (DMN), saliency network (SN), and dorsal attention network (DAN).…”
Section: Introductionmentioning
confidence: 99%